Baltic amber: A new Cacomorphocerus Schaufuss, 1892 with two specimens preserved in a single piece, and four new Malthodes Kiesenwetter, 1852 - Parisi, Francesco; Fanti, Fabrizio (Zootaxa, 2020)
The Baltic amber has proven to be an incredible resource for the environmental and faunistic diversity of the Eocene and this is also evident from the vast amount of Cantharidae species (soldier beetles) described as inclusions in this resin and Fossil-Lagerstätte. The present work contributes to highlighting both this trend and the variety of forms in particular for the genus Malthodes Kiesenwetter, 1852 with four new species described and with the addition of a new species of Cacomorphocerus Schaufuss, 1892 with two specimens included in the same amber piece. The new forms, described and illustrated here, are: Cacomorphocerus obstinatus sp. nov., Malthodes giannii sp. nov., Malthodes immortalis sp. nov., Malthodes marialuisae sp. nov., and Malthodes unimol sp. nov.